Handbook of research on microbial remediation and microbial biotechnology for sustainable soil - Malik, Junaid Ahmad, 1987- (Advances in environmental engineering and green technologies (AEEGT) book series., 2021)
"This book highlights some of the significantly important microbial species involved in remediation, the physiology, biochemistry and the mechanisms of remediation by various microbes, and suggestions for future improvement of bioremediation technology"--